Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1021/bm060464a
|View full text |Cite
|
Sign up to set email alerts
|

Designer Protein-Based Performance Materials

Abstract: Repeat sequence protein polymer (RSPP) technology provides a platform to design and make protein-based performance polymers and represents the best nature has to offer. We report here that the RSPP platform is a novel approach to produce functional protein polymers that have both biomechanical and biofunctional blocks built into one molecule by design, using peptide motifs. We have shown that protein-based designer biopolymers can be made using recombinant DNA technology and fermentation and offer the ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 36 publications
(48 reference statements)
0
15
0
1
Order By: Relevance
“…Designed repeat sequence protein polymers can be isolated to obtain performance materials having both biomechanical and biofunctional blocks built into one molecule, and these could have applications in biodefence, industrial biotechnology and personal care areas. 31 High molecular mass protein polymers can be designed to self-assemble in solution to form transparent, selfsupporting gels that have a high degree of elasticity. 32 A disulfide-bridged protein polymer of α s1 -casein was constructed by chemical introduction of thiol groups into its lysine residues.…”
Section: Introductionmentioning
confidence: 99%
“…Designed repeat sequence protein polymers can be isolated to obtain performance materials having both biomechanical and biofunctional blocks built into one molecule, and these could have applications in biodefence, industrial biotechnology and personal care areas. 31 High molecular mass protein polymers can be designed to self-assemble in solution to form transparent, selfsupporting gels that have a high degree of elasticity. 32 A disulfide-bridged protein polymer of α s1 -casein was constructed by chemical introduction of thiol groups into its lysine residues.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to measurements, each sample was diluted by adding water to the appropriate dilutions. In addition, the metal binding capability of free triblock copolymer in aqueous solution as well as (His) 6 (VPGVG) 78 (His) 6 constructed previously 11 were examined. Ten nanomoles of biopolymers was used in the experiments, and the same procedures were performed.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…4 Because of the sequence-directed control over structure and property as well as their intrinsic stimuli-responsive selfassembly capability, protein copolymers based on ELP sequences have been attracting attention as novel biomaterials. 6 A logical extension in expanding the types of application is to introduce additional functionalities into this self-assembled peptide system. Previously, we have demonstrated that ELPs can be engineered to integrate multifunctionalities while preserving the phase-transition property.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A set of overlapping primers will reconstitute the desired gene in a two-step PCR method known as gene assembly or gene synthesis (1,2). However, for genes with multiple identical domains or internal sequence repeats, which have gained increased interest as models for repeat proteins (3,4) and as designed proteins (5), this method of gene synthesis may fail due to mispriming. This drawback might be avoided by synthesis of alternative primers for each domain due to the degenerated genetic code (6), but with increasing numbers of domains, the variability of the oligonucleotides will be exhausted.…”
mentioning
confidence: 99%